Efisiensi Alokatif Budidaya Karet di Kecamatan Sungai Ambawang Kabupaten Kuburaya - Panggabean, Leonardi; Suyatno, Adi; Suharyani, Anita (Fakultas Pertanian Universitas Tanjungpura, 2023)
This study aims to analyze the factors that influence rubber production and to analyze the efficiency of the price of rubber production. The variables examined in this study include the efficiency of the use of rubber production factors, the Cobb-Dounglas production function is unsed, Classic Assumption Test, Statistical Test and Allocative Efficiency. The test results on the production factors show that the variable area of land.Labor, fungicide had a significant effect on production. NPK fertilizer and length of farming had no significant effect on rubber production. The results of the allocative efficiency analysis showed that the use of land area, labor and fungicides was inefficient in rubber cultivation in Ambawang district, Kubu Raya Regency.